2019
DOI: 10.21873/anticanres.13593
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor as a Biomarker of Oral Squamous Cell Carcinoma Progression Risk

Abstract: Background/Aim: Oral squamous cell carcinoma (OSCC) is a cancer with poor prognosis due to therapy resistance, locoregional recurrences, and distant metastases. There is on increased interest in profiling the androgen receptor (AR) in cancer biology. The aim of this study was to compare AR and Ki-67 levels in the neoplastic epithelium and stroma between non-metastatic and metastatic stages of OSCC. Patients and Methods: Tissue specimens of 101 nonmetastatic and 95 metastatic OSCC patients were analyzed by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The identification of sensitive biomarkers was very important for the improvements of the clinical outcome of OSCC patients [21,22]. There have been many papers reporting the discovery of OSCC biomarkers, but only a few biomarkers have been validated and successfully applied in routine clinical practice [23,24]. Moreover, most biomarkers possess limitations for the early detection of OSCC, and their prognostic value was plagued by inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of sensitive biomarkers was very important for the improvements of the clinical outcome of OSCC patients [21,22]. There have been many papers reporting the discovery of OSCC biomarkers, but only a few biomarkers have been validated and successfully applied in routine clinical practice [23,24]. Moreover, most biomarkers possess limitations for the early detection of OSCC, and their prognostic value was plagued by inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Effective tumor markers can reduce tumor recurrence rate and increase survival rate; finding such markers could provide important guidance for clinical treatment [25]. Even though many new OSCC biomarkers have been identified in recent years [26][27][28], their mechanisms remain unclear. As an emerging tumor biomarker, LINC01303 has been extensively studied, but its role in OSCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Those in vitro observations also associated AR signalling with enhanced cell migration, potentially increasing tumour aggressiveness. Another recent study using a larger cohort (total n=196) of metastatic and non-metastatic OSCC patients suggested that AR cytoplasmic accumulation associates with moderately increased risk of metastasis (78). The significance of AR cytoplasmic immunostaining in this context requires additional clarification, especially considering that AR splice variants play an important role in prostate cancer and some of those variants may accumulate in the cytoplasm (Zhan et al, 2017) (79).…”
Section: Hormone Receptors In Hnsccmentioning
confidence: 99%